Impact of COVID-19 Pandemic on Trauma CT Imaging - Yi Yan; Kai Hu; Kevin Shek; Jun Li; Shady Attalla; John Ross Bonanni; Jai Jai Shankar; Lisa McPhee (Radiology Research and Practice)
Purpose. The goal of this study was to understand the impact of COVID-19 pandemic and associated lockdown measures on the volume, rate, and type of trauma presenting to the emergency department (ED) by using trauma-initiated CT studies to capture patient data. Materials and Methods. We performed a retrospective observational study comparing patients undergoing CT scans for trauma during the 1st and 2nd lockdown periods compared to corresponding prepandemic months. During two lockdown periods, public places such as restaurants, libraries, parks, and shops across the province were shut down. Government-led messaging advised that people should stay at home and practice social distancing. The rate of trauma-initiated CT scans and the proportion of different types of traumas were compared between time periods. Results. There was no significant difference in overall trauma-initiated CT scans between the prepandemic and pandemic levels. Motor vehicle collision (MVC) cases decreased from 18.2% to 15.6% during the first lockdown period (p = 0.049) and also reduced from 29.1% to 25.2% during the second lockdown period (p = 0.013). Trauma from falls increased from 19.1% to 27.5% (p = 0.036) during the first lockdown, despite no significant change during the 2nd lockdown. Furthermore, the percentage of stab injuries increased from 25.0% to 38.9% while blunt trauma decreased from 68.5% to 54.3% during two lockdowns (p = 0.015). Conclusion. The total number of trauma-initiated CT scans did not significantly decrease during the lockdown periods. Stabbings and falls increased during lockdown periods while MVCs and blunt trauma decreased.